(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article emphasizes the importance of engaging with diverse English varieties and accents to enhance communication skills, promote cultural understanding, and foster inclusivity. It explores how accents reflect the rich histories and identities of their speakers, highlighting examples from British, American, Australian, Caribbean, and Asian Englishes. The piece provides practical tips for improving listening skills, such as consuming global media, practicing active listening, and engaging in conversations with speakers from various linguistic backgrounds. The conclusion reinforces the value of embracing linguistic diversity as a pathway to mutual respect and global connection. Through this perspective, the article underscores that language is not just a tool for communication but also a celebration of humanity’s